The adoption of green information technologies and systems as a driver within green SCM - Savita, K.S. (Institute of Electrical and Electronics Engineers Inc., 2014)
Information Technology (IT) and Information System (IS) have begun to demonstrate their role in motivating, enabling, and transforming Supply Chain Management (SCM) towards ecological sustainability. The relationship between SCM, IT, IS and environmental sustainability are complex but interdependent to an extent for a greater energy and environmental efficiency. Most companies typically disregard the need to adopt, assess and report on the impacts of IT and IS for environmental sustainability. This paper discusses on cognitive interviewing procedures conducted and preliminary findings obtained from semi-structured interview with three of the ISO 14001 manufacturing companies in Perak as the input for the full scale main study. During cognitive interview, both the think aloud and probing method were used that have leads to number of amendments to the survey questionnaire. The preliminary discoveries from the semi-structured interview reveal that IT and IS play a greater role in environmental sustainability among ISO14001 manufacturing company in Malaysia. The role of IT and IS for environmental sustainability are deem as a necessity in enhancing flexibility and visibility in decision making as well as in minimizing energy consumption, carbon footprint and e-waste disposal. The decision on implementing IT and IS for environmental sustainability are highly dependent on the trade-off between costs and gains. This is because the implementation of information technologies might not produce the immediate benefits or required payback, as compared to information systems which are more apparent. These situation is further aggravated with poor assessments on the performance the information technology and systems invested. Â© 2014 IEEE.